THE URGENCY OF STRENGTHENING APPRAISAL REGULATIONS TO REALIZE A LEGAL PROTECTION FOR APPRAISER - Abubakar, Lastuti; Handayani, Tri (Media Hukum, 2019)
To provide legal protection and legal certainty for service users and Appraisers, the Government, in this case, the Ministry of Finance requires the Public Appraisal profession to obtain a permit in supporting financial service sector. The research describes the position and responsibility of Appraisers in assessing collateral for loan and  finance, that in practice, often requires Appraisers? administrative, civil, and criminal responsibilities. The article uses a multi-interdisciplinary approach by applying status, comparative, and case study. The results show that a key for legal protection for appraiser comes from a legal relationship between an Appraiser and a Bank. The assessment of collateral for bank loan and financing, arises from collateral appraisal cooperation agreements; and from the legal provisions, including Regulation of the Ministry of Finance on Public Appraisal and the other related Laws. Furthermore, Legal responsibility of Appraiser's mistakes in appraising will be an administrative and civil sanctions. To provide legal certainty and legal protection for the Appraisal profession requires a strengthening of regulations by the issuance of Law on Public Appraisers such as other supporting professions, namely Public Notary, Legal Consultant, and Public Accountant.